War, image and legitimacy viewing contemporary conflict - Michalski, Milena; Gow, James (Contemporary security studies, 2007)
Drawing on a wide range of examples from fiction and factual film, current affairs and television news, as well as new digital media, this book examines how image affects war and whether image affects our understanding of war.